Some properties of kenaf and kenaf/cotton combing waste composites / Wan Yunus Wan Ahmad … [et al.] - Wan Ahmad, Wan Yunus; Salleh, Jamil; Yahya, Mohd Faizul; Abdul Kadir, Muhammad Ismail; Misnon, Mohd Iqbal (2004)
Kenaf is one of the most promising fibers for composite conversion. In this work, kenaf is being combined with combing waste and polyester resin as matrix. The comparison of properties are based on tensile strength and flexural strength of 100% resin, 100% kenaf and 50/50 kenaf/cotton combing waste in three types of lay-ups of longitudinal, cross-laid and transverse. Interesting , y the highest results of tensile and flexural strength are from different lay-ups of composites. The tensile and flexural strength properties are also compared with similar properties on glass composites.